An experimental investigation into the pre-treatment of synthetic membranes using sodium hydroxide solutions - Jones, Sarah A.; Bird, Michael R.; Pihlajamäki, Arto (Journal of food engineering, 2011)
In this paper the effect of two pre-treatment methods are compared experimentally for the filtration of (i) a spent sulphite liquor (17.8 wt.% dry solids) using a 20 kg mol −1 molar mass cut off (MMCO) fluoropolymer membrane and (ii) a molasses solution (45° Brix) using a polysulphone (Ps f) membrane (1.5 μm pore size). Both feeds are industrially relevant, and subject to severe fouling issues when membranes are used in their subsequent processing. The pre-treatment methods evaluated were: (i) conditioning with water at 60 °C only [Protocol 1], and (ii) conditioning with water at 60 °C followed by cleaning with 0.5 wt.% NaOH [Protocol 2]. Results are presented that confirm the benefits of sodium hydroxide preconditioning upon performance, supporting the suggestion by some membrane manufacturers that this step be included as part of the pre-treatment protocol.